Screening gender on children's television the views of producers around the world - Lemish, Dafna 1951- (London Routledge, 2010)
This text offers readers insights into the transformations taking place in the presentation of gender portrayals in television productions aimed at younger audiences. It shares media professionals' action-oriented recommendations for change that would promote gender equity, social diversity and the well-being of children.
Gender representations and their socializing role: what do we already know? : Features of gender representations in children's visual media ; Theoretical conceptualization and framing ; Construction of gendered identities and roles ; Asking new questions -- Studying producers of quality television around the globe: methodological issues : Quality television for children ; The events ; The interviewees ; The interview ; Presentation of results -- What does gender mean?: Understanding gender in cultural context : Introduction ; Gender between a rock and a hard place: the local and the global ; Local cultural perspectives of gender -- The big no-no: sex and sexualities : Sex and the media ; Discussing sex and sexualities ; Sex on television as a taboo ; Homo/lesbian sexualities ; Sexual abuse ; Girls: an integrated case study in the representation of sex -- The segregated workplace and the implied audience : Gendered workplace ; The implied audience -- Gender representations in children's television:eight working principles for change : Equality ; Diversity ; Complexity ; Similarity ; Unity ; Family ; Authenticity ; Voicing -- Beyond the principles: concluding notes on changing gender representations : Toward gender equality in children's television ; The power of imagination -- Glossary of programs.
Based on the author's interviews with 135 producers of children's television from 65 countries, the book discusses the role television plays in the lives of young people and, more specifically, in developing gender identity.
Keywords: Television and children; Children's television programs -- Social aspects; Gender identity on television; Sex role on television